1997
DOI: 10.1017/s146239949700001x
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus 6

Abstract: Human herpesvirus 6 (HHV-6) is a T-lymphotropic herpesvirus, which infects almost all children by the age of two years and persists lifelong. Two distinct variants of HHV-6, HHV-6A and HHV-6B, have been described, and the latter has been shown to be a common cause of acute febrile illnesses in young children, including exanthem subitum (roseola). HHV-6 has also been associated with a number of neurological disorders, including encephalitis and seizures, and the virus has been postulated to play a role in acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
5

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
0
8
0
5
Order By: Relevance
“…A number of studies have suggested that the central nervous system is the site of persistent HHV-6 infection [3,[6][7][8][9]. However, only 3 cases of ocular inflammation-associated HHV-6 have been reported [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have suggested that the central nervous system is the site of persistent HHV-6 infection [3,[6][7][8][9]. However, only 3 cases of ocular inflammation-associated HHV-6 have been reported [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…HHV-6 infects almost all children by the age of 2 years and persists for a lifetime [3]. HHV-6 is the cause of exanthema subitum in children [4].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have suggested that the central nervous system can be a site for persistent HHV-6 infection [1,3,4,6,7]. Challoner et al [1] described plaque-associated expression of HHV-6 in multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…HHV-6 is a T-lymphotropic herpesvirus, which infects almost all children by the age of 2 years and persists lifelong [3]. Prospective studies have shown that HHV-6 is the most common pathogen responsible for febrile illness in infants and in some infants is associated with febrile convulsions [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation